Basic verbal skills for music therapists - Schwartz, Elizabeth (Elizabeth K.) (Barcelona Publishers, 2019)
"The focus [of this book] will be to give music therapy students and young professionals a road map for deciding why, when, and how to use basic verbal skills in their work."--Introduction